HATE SPEECH DALAM PANDANGAN UU ITE DAN FATWA MUI - Wulandari, Fajrina Eka (IAIN Tulungagung, 2017)
The article discussed about the dissemination of hoax news that contain hate speech. The method used in this article is library research because the case is actual cases. Hate speech based on information dan electronic transactions lawis prohibibted and given a strict punishment for the perpetrators. The MUI has also forbid hate speech.Keywords: Hate Speech, UU ITE, MUI Pendahuluan